Epidemiology of injuries among children and adolescents from the Xinglin District in Xiamen, 2016–2019 - Lin, Gangxi; Zeng, Qiyi (Frontiers in Pediatrics, 2024)
Objective: To investigate the epidemiology of injuries among children and adolescents in the Xinglin District of Xiamen from 2016 to 2019. Methods: This study collected data from patients who attended the outpatient and emergency departments of the Xinglin District at the First Affiliated Hospital of Xiamen University between January 2016 and December 2019, diagnosed with injuries. Results: A total of 13,123 patients were included, categorized into age groups 0-4 (n=4834), 5-9 (n=3924), 10-14 (n=2671), and 15-18 (n=1694). The rates of unintentional injuries were 97.00%, 96.94%, 94.50%, and 90.08% in the 0-4, 5-9, 10-14, and 15-18 age groups, respectively (P<0.001). The proportion of head injuries decreased with age (from 41.13% in the 0-4 age group to 18.00% in the 15-18 age group), compensated by an increase in rates of injuries to upper and lower extremities and multisite injuries (P<0.001). The most common causes of injuries were fall-related injuries (30.46%-52.05%), followed by mechanical injuries (18.35%-36.42%), with the rates of fall-related injuries decreasing with age and rates of mechanical injuries increasing with age (P<0.001). Age-period-cohort models revealed that the time factor was not significant for fall-related injuries and mechanical injuries (all P>0.05) despite apparent increases in incidence over time. Conclusion: Injuries in children and adolescents continue to be a significant public health concern in the Xinglin District (China), predominantly driven by fall-related injuries and mechanical injuries.